The effect of plant growth regulators on height control in potted Arundina graminifolia orchids (Growth regulators in Arundina graminifolia) - Christina da Silva Wanderley; Ricardo Tadeu de Faria; Mauricio Ursi Ventura; Wagner Vendrame (Acta Scientiarum. Agronomy, 2014)
Orchids have become an important portion of the international floriculture market.  Arundina graminifolia is a terrestrial orchid that produces attractive flowers, and, although the species could be a potential candidate for the floriculture market, its considerable height makes it difficult to transport and commercialize.  A number of plant growth regulators have been utilized to control plant height in ornamentals and other species.  Thus, the aim of this study was to evaluate the efficiency of growth regulators, paclobutrazol and chlormequat chloride on the vegetative development of containerized A. graminifolia orchid aiming at height control.  Paclobutrazol (Cultar) was applied at 0, 5, 10, and 20 mg L-1, and CCC (Cycocel) was applied at 0, 2000, 4000, and 6000 mg L-1. The plants were assessed monthly for the plant height and number of shoots per container. CCC had no effect on the final height of plants at the concentrations applied. In contrast, paclobutrazol was effective in controlling plant height at a concentration of 5 mg L-1, but higher concentrations (10 and 20 mg L-1) proved to be toxic to the plants, causing death to the new shoots. Paclobutrazol at lower concentrations offers a viable means for height control in A. graminifolia.